Fewer S‐alleles are maintained in plant populations with sporophytic as opposed to gametophytic self‐incompatibility. Issue 1 (13th August 2012) - Busch, Jeremiah W.; Witthuhn, Tyler; Joseph, Michael
Abstract Plants use self‐incompatibility to reject pollen bearing alleles in common at the S‐locus. These systems are classified as gametophytic (GSI) if recognition involves haploid pollen or sporophytic (SSI) if recognition involves diploid paternal genotypes. Dominance in SSI systems reduces the number of S‐alleles, but it has not been clear which system should maintain greater diversity when all else is equal. We simulated finite populations to compare the equilibrium number of S‐alleles in populations with either GSI or a co‐dominant SSI system. When population size was constant, SSI systems maintained more S‐alleles than GSI systems. When populations fluctuated in response to an S‐Allee effect, fewer S‐alleles were observed in SSI systems when S‐allele diversity was low, and SSI populations were vulnerable to extinction over a broader range of parameters. Turnover rates at the S‐locus were also faster in SSI populations experiencing strong S‐Allee effects. Given the variable expectations concerning S‐allele diversity in these systems, we reviewed published estimates of S‐allele diversity. GSI populations have significantly more S‐alleles on average than SSI populations (GSI = 25.70 and SSI = 16.80). Dominance likely contributes to this pattern, although the demographic consequences of the S‐Allee effect may be important in populations with fewer than 10 S‐alleles.